ТЕРМОМЕТРИЧНІ МЕТОДИ ДОСЛІДЖЕННЯ СТАНУ СПРЕСОВАНОСТІ ОСЕРДЯ СТАТОРА ПОТУЖНОГО ТУРБОГЕНЕРАТОРА - Зайцев, Є. О.; Панчик, М.В. (Інститут електродинаміки Національної академії наук України, 2021)
The article is devoted to the analysis of thermometric methods of control and diagnosis of the state of compression of the stator core of the turbogenerator (TG), which have found the greatest application. It is shown that ensuring effective and high-quality control of powerful electric machines, especially power plant generators, today is an integral part of ensuring the reliability and trouble-free operation of their work. As a result of the analysis, it is shown that ensuring high reliability of operation of the generating equipment is practically impossible without their equipping with modern means of control capable to work in real-time. Bibl. 34, fig. 4.